Intravaginal nonablative radiofrequency in the treatment of genitourinary syndrome of menopause symptoms: a single-arm pilot study - Cintia Pinheiro; Teresa Costa; Raira Amorim de Jesus; Raquel Campos; Rosa Brim; Alcina Teles; Andrea Vilas Boas; Patrícia Lordêlo (BMC, 2021)
Abstract Background Genitourinary syndrome of menopause (GSM) involves vaginal dryness (VD), pain during sexual activity (SAPain), vaginal itching (VI), burning, pain, and symptoms in the urinary organs. Non-ablative radiofrequency (RF) is a type of current with electromagnetic waves with a thermal effect that generates an acute inflammatory process with consequent neocolagenesis and neoelastogenesis. We aimed to describe the clinical response to VD, SAPain, vaginal laxity (VL), VI, burning sensation, pain in the vaginal opening, urinary incontinence, sexual dysfunction, cytological changes, and adverse effects of non-ablative RF in patients with GSM. Methods This single-arm pilot study included 11 women diagnosed with GSM with established menopause. Patients with hormone replacement initiation for six months, who used a pacemaker, or had metals in the pelvic region, were excluded. Subjective measures (numeric rating scale of symptoms, Vaginal Health Index-VHI) and objective measures (vaginal maturation index-VMI, vaginal pH, sexual function by the FSFI, and urinary function by the ICIQ-SF) were used. A Likert scale measures the degree of satisfaction with the treatment. Five sessions of monopolar non-ablative RF (41°C) were performed with an interval of one week between each application. The entire evaluation was performed before treatment (T0), one month (T1), and three months (T2) after treatment. Adverse effects were assessed during treatment and at T1 and T2. Results The symptoms and/or signs were reduced after treatment in most patients (T1/T2, respectively): VD 90.9%/81.8%, SAPain 83.3%/66.7, VL 100%/100%, VI 100%/100%, burning 75%/87.5%, pain 75%/75%, and VHI 90.9%/81.9%. Most patients did not show changes in VMI (54.5%) and pH (63.6%) at T1, but there was an improvement in VMI in most patients (54.5%) at T2. Nine patients were satisfied, and two were very satisfied at T1. The treatment was well tolerated, and no adverse effects were observed. There was an improvement in sexual function (72.7%) and urinary function (66.7% in T1 and 83.3% in T2). Conclusion Intravaginal RF reduced the clinical symptoms of GSM in most patients, especially during T1, and women reported satisfaction with treatment. The technique showed no adverse effects, and there were positive effects on sexual and urinary function. Trial registration This research was registered at clinicaltrial.gov (NCT03506594) and complete registration date was posted on April 24, 2018.